THE RELATIONSHIP OF SELECTED VEGETABLE FARMERS’ CHARACTERISTICS AND THEIR KNOWLEDGE ABOUT VEGETABLE FARM MANAGEMENT IN KENDARI, SOUTH-EAST SULAWESI - Sukmawati Abdullah; Amri Jahi (Jurnal Penyuluhan, 2006)
Should the vegetable farmers’ knowledge be improved when their productivities did not meet the community expectation? This question led to the to the following research objectives: (1) to determine the vegetable farmers’ distribution on selected characteristics; (2) to identify their current knowledge on vegetable farm management; and (3) to assess the extent of relationship amongst the farmers’ characteristics and their perceived knowledge on vegetable farm management. To meet these objectives, This research was designed as a descriptive-correlation study. The independent variables of this study were the farmers’ characteristics and the dependent variable was the farmers’ perceived knowledge on vegetable farm management. The population of the study was 517 vegetable farmers that resided in six sub-districts in the city of Kendari; whereas the sample was 99 farmers selected randomly from the obtained stratified population. They were interviewed in February through March 2006. Data were analyzed using descriptive statistics and Kendall Concordant W procedures. The study concluded that: (1) most of the vegetable farmers observed in the study: were old, had primary school education, had long farm experiences, had relatively wide vegetable farms, had sufficient working capital, had enough family members, consumed enough media, had frequent contact with Extension agents, were aware of market information, had several farm tools and equipments, had high income, and husband mostly made farm decisions, (2) considered marketing of farm produce, use of farm technologies, and constraints and opportunities for farm produce development as the three most important knowledge, (3) farmers mostly agreed to the rank order of the nine vegetable farm management knowledge fields.